The Subjective Perception of Employment Instability: Is It Bad to Be Unstable? - Elena Gasiukova; Anastasia Petrova (Journal of Economic Sociology, 2021)
Nowadays in the literature, there are two perspectives on the spread of atypical labor contracts and unstable employment trajectories: some authors insist on the vulnerability of modern employees and the weakening of their bargaining position; others emphasize new opportunities for flexibility and independence from the employer. However, it remains unclear how employees react to these new employment conditions. Is instability a benefit or a sign of vulnerability for them? This discussion is most relevant for skilled young workers, as freedom and flexibility are of great value to them. The authors make an attempt to discover which position is closer to unstable workers in Russia. The Russia Longitudinal Monitoring Survey—Higher School of Economics (RLMS-HSE) data for 2014–2018 were used for the analysis. The panel data was used to construct the variable of instability in the labor market, taking into account the previous working status of the respondents (the sample size was 1,507 respondents). The main method of analysis was linear regression. The dependent variables were the components of subjective well-being, and the explanatory variable was the status of employment instability. The results show that employment instability is not related to respondents’ subjective well-being, nor to job insecurity. No differences in the subjective assessments of stable and unstable employees with different skills and income levels were found. The findings allow us to state that employment instability is not perceived by Russian employees as a distinct situation in the labor market, or as referring to negative or positive type of work or social position of an individual.